Use of mobile technologies by business companies in the context of digitalization of the Latvian economy - Olga Lavrinenko; Alina Danileviča; Ilona Jermalonoka; Alina Betlej; Oksana Ruža; Marija Sprūde (Entrepreneurship and Sustainability Issues)
The article aims to identify the factors contributing to the development of mobile technologies among Latvian entrepreneurs. The limited spread of mobile technologies can lead to issues in Latvia's economy, like limited access to digital services and resources, a decline in competitiveness between enterprises, limitations in the case of innovation, and unavailability of economic growth. Suppose the use of mobile technologies stays limited in certain areas or between certain groups of people. In that case, it can lead to unequal conditions for information, education, work opportunities and new businesses. With mobile technologies, Latvia can achieve a digital transformation in economics, leading to an advantage in digital economics compared to other countries. With the use of analyzed data from the questionnaire that was given to Latvian entrepreneurs, as well as the analysis of literature sources, the authors emphasize the importance of informative and technological development, IT specialist qualifications and digital literacy for the development of the digital economy, as it can be seen that high digital literacy and availability of IT infrastructure can stimulate economic growth, although, the deficit of qualification can become a big obstacle. The drawn conclusions emphasize the importance of work in terms of information about the advantages of digital technologies among small and average entrepreneurs. Further research can be focused on rating the effectiveness of specific programmes about digital literacy and the availability of IT infrastructure in the context of the Latvian economy.